Using the local positioning system based on Pulse Width Modulation for Robot Positioning - F Masoudifar; MA Nekoui (Journal of Applied Sciences and Environmental Management, 2011)
There are many ways to estimate the location of a moving object. One way is to determine its location using a GPS which calculates longitude and latitude of the object by the data received by the satellites rotating around the earth. However, there are no devices to recover calculated inherent errors and have an appropriate estimated signal. From robots' place, we should correct the errors made by collected data from sensors. A problem happening alternatively in the landmark identifying a method is the similar sharing data. The data obtained should be related to correcting land mark. Even though, some landmarks are likely to be similar. In addition, it is impossible to guarantee sightseeing line among landmarks in some arrangements. The other methods are to utilize radio frequency stations, which are placed around the robot by which we can find the real place of source of measurement error. In non-isolated environments, due to noises in signals using such a system should be investigated. In this PAPER, LPS (local positioning system) and the way it influences interference signals on the simulated system has been studied. A method has been tried to present in order to decrease destructive effects of noise using GA (genetic algorithm). In this way, the LPS modulation method and factors which cause interference signal and noises in the system have been stated. The obtained results have been illustrated by different simulations followed by discussions.